Potensi Ekstrak Choromolaena odorata dan Mikaina micrantha Sebagai Antikanker - Ryadi, Yusuf; Batubara, Irmanida; Mariya, Silmi; Saifanah Setiawan, Nabilah (Politeknik Kesehatan Kemenkes Bengkulu, 2024)
The Asteraceae family has beneficial medicinal effect as anticancer, such as Chromolaena odorata and Mikaina micrantha. This study we investigated the potency of two Asteraceace plants and determined their active compounds. The plants were extracted using distilled water and then fractionated with chloroform. The phytochemical content, and anticancer potency was determined by literature study. The results showed that both plants contained essential oils, flavonoids, phenolics, terpenoids, and steroids. Toxicity to shrimp larvae through the Brine Shrimp Lethality Test (BLST) showed that both plants were toxic , so they were thought to be anticancer. Ombuin and vanylic acid compounds in C. odorata are reported its bioactive compound has activity anticancer. M. micrantha has less potential as an anticancer and more activity as an anti-inflammatory.